Mechanical performance of date palm fiber-reinforced concrete modified with nano-activated carbon - Adamu Musa; Ibrahim Yasser E.; Ahmed Omar Shabbir; Drmosh Qasem A. (Nanotechnology Reviews, 2023)
Date palm fiber (DPF) is an easily processed, low cost, and accessible natural fiber. It has mostly been used in composites for non-structural applications. For DPF to be utilized in cementitious composites for structural applications, ways to reduce its harmful effect on compressive strength must be devised. Therefore, in this study, nano-activated carbon (NAC), due to its filler effects, was used as an additive to produce the DPF-reinforced concrete (DPFRC). To produce the DPFRC, 0, 1, 2, and 3% by cement weight of DPF and NAC were added. The fresh properties, strength, and microstructure of the concrete were examined. The findings revealed that DPF decreased the consistency, density, and compressive strength. Additionally, it increases the porosity in the concrete microstructure. The addition of up to 1% NAC significantly improved the compressive, flexural, and split tensile strengths of the concrete, while it decreased the harmful impact of up to 2% DPF on the DPFRC’s strength. The split tensile and flexural strengths of the concrete were enhanced with the addition of up to 2% DPF without any NAC. The addition of up to 2% NAC densified the DPFRC’s microstructure by refining and filling the pores generated by the DPF. The multivariable statistical models developed to estimate the mechanical properties of the DPFRC containing DPF and NAC were very significant with a very high degree of precision.